Pengaruh Board Size, Independensi Komite Audit dan Profitabilitas terhadap Ketepatan Waktu Laporan Keuangan - Fahmi, Cecilia Hanifah; Setiawan, Mia Angelina (Jurnal Nuansa Karya Akuntansi, 2024)
The goal of this study is to investigate the relationship between financial report timeliness and board size, audit committee independence, and profitability. Consumer cyclical companies registered on the Indonesia Stock Exchange between 2018 and 2022 comprise the study's population. Purposive sampling is the method used in the study to collect research samples. Using the SPSS 24 software, multiple linear regression analysis was the data analysis method applied in this study. The findings demonstrated a negative and significant impact on the timeliness of financial reports on board size, audit committee independence, and profitability. It is anticipated that additional variables influencing the timeliness of financial reports would be selected for future study.